Study on Urban Planning and Construction Management Institution of Modern Tianjin - Liu, Qingyue; Li, Dongwei; Song, Kun; Wang, Jianghua (International Planning History Society Proceedings, 2016)
After the Second Opium War in 1860, Tianjin was opened as a treaty port of China. From 1860 to 1902, nine foreign countries had set up concessions in Tianjin. They are British, France, US, German, Italia, Japan, Russia, Austria and Belgium. Tianjin became the city which had the most concessions in China. Since then, the import of modern urban planning theory and management regime from the western countries had a profound effect on the urban planning and construction in Tianjin. Great changes had taken place on land consolidation, real estate development, urban construction, spatial planning, and construction management. This paper focuses on the organization structure of the urban planning and construction management institution， management principles, government laws, land policy in Tianjin from 1860 to 1945. It highlights the transformation of urban planning and construction management organization in concessions and native area in Tianjin during that time. As the first established concession in Tianjin, the British Concession followed the public concession of Shanghai, founding the municipal committee to supervise urban construction. Subsequently, other concessions set up their respective management institutions. And the Tianjin Provisional Government was the first to apply management mode of the concessions into Chinese native area. This paper explores how the western urban construction management system was introduced into concessions in Tianjin, and how it was applied in the construction and management of Chinese section in Tianjin based on a wealth of collected information. Such as historical archives, historic documents, old postcards, old pictures from Tianjin Municipal Archives and previous research works. From the perspective of city planning and construction management system, this paper reveals the causes and process of transformation of urban construction in modern Tianjin. At the same time, it further analyses the important influence and effect of the introduction of western urban construction management mode on urban construction in Tianjin. Finally, it reaches a conclusion that all the changes which happened in modern Tianjin not only transformed the boundary and spatial structure of this city, but also affected the pattern of development and management in Chinese section. From then on, a new chapter of urban construction for modern Tianjin has been opened.